Analisis Manajemen Risiko pada UMKM Konveksi YouthStruggle (YS), Tanjungsari, Kabupaten Sumedang - Mubarrok, Muhammad Luthfi; Zaki, Muhammad; Maulana, Asep Rizal; Meijaya, Panji Setia; Alfiana, Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
YouthStruggle (YS), a micro-scale garment business established in 2023 in Jl. Mandi, Tanjungsari, faces various business risks due to market dynamics and its labor-intensive production process. This study aims to identify operational, financial, human resource, and market risks in YS and determine appropriate mitigation strategies. The research employs a qualitative descriptive approach through observations, semi-structured interviews with the owner, and documentation of production activities. Data were analyzed using the Miles and Huberman model and a 3×3 risk matrix. The findings reveal that the most prominent risks occur in operational activities, including delays in raw material supply, machine breakdowns, and inconsistent product quality. Financial risks arise from limited capital and manual bookkeeping, while human resource risks relate to low skill levels and worker turnover. Market risks stem from changing fashion trends and competition from imported products. Most risks fall into the high category, requiring immediate mitigation. Recommended strategies include supplier diversification, scheduled machine maintenance, skills training, financial digitalization, and strengthened digital marketing.